ANALYSIS FACTOR OF UMROH / HAJI BUREAU LOCATION SELECTION IN MALANG - Fien Zulfikarijah; Tsabita Khwarazmita (Journal of International Conference Proceedings (JICP), 2019)
The aim of the study was to develop a factor in selecting the business location of the Umrah Bureau in Malang through exploration of indicators and variables and finding new factors. Population and sample of study 41 respondents were administrators / owners of the Umrah Bureau both head office, branch and agent in Malang. Based on the results of the recapitulated questionnaire and fulfilled the requirements for analysis of 32. The analytical method uses factor analysis with the Explore Factor Analysis (EFA) approach, which collects respondents' responses to the variables and indicators of site selection first then processes through the factor analysis stages. The results of data analysis found 5 variables that were considered in choosing the business location of the umroh bureau, namely infrastructure, employment, community attitudes, costs and markets. These variables are translated into 14 indicators. Of the 14 selected indicators, there are 7 indicators with 2 new naming factors, namely the main facilities and supporting facilities. The main facilities factor consists of the availability of educated labor, the level of labor productivity, proximity to Islamic education institutions such as schools and huts, availability of roads and electricity. Factors supporting facilities that consist of ease of accessing information technology and business location security.